2018
DOI: 10.1017/s003329171800034x
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence for discrete neurocognitive subgroups in patients with non-psychotic major depressive disorder: clinical implications

Abstract: These results suggest the presence of multiple neurocognitive subgroups in non-psychotic MDD with unique profiles, one of which exhibits deficits comparable to those of schizophrenia. The results of the present study may help guide future efforts to target these disabling symptoms using different treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 95 publications
(120 reference statements)
2
34
1
1
Order By: Relevance
“…Only two studies have been carried out clustering analysis with exclusively MDD patients, and their findings point toward cognitive heterogeneity along the different stages of the disorder. One included patients in partial remission and reported three clusters (Pu et al, 2018) in accordance with the above-mentioned studies, and the other was centered into first-episode patients and showed two clusters, one preserved and one impaired (Vicent-Gil et al, 2018). These previous studies, except for the one with firstepisode patients, endorse our current findings of a subgroup of intact or mostly preserved patients, of a globally impaired subgroup with a general cognitive affectation, and of a subgroup with specific domains impaired.…”
Section: Discussionsupporting
confidence: 89%
“…Only two studies have been carried out clustering analysis with exclusively MDD patients, and their findings point toward cognitive heterogeneity along the different stages of the disorder. One included patients in partial remission and reported three clusters (Pu et al, 2018) in accordance with the above-mentioned studies, and the other was centered into first-episode patients and showed two clusters, one preserved and one impaired (Vicent-Gil et al, 2018). These previous studies, except for the one with firstepisode patients, endorse our current findings of a subgroup of intact or mostly preserved patients, of a globally impaired subgroup with a general cognitive affectation, and of a subgroup with specific domains impaired.…”
Section: Discussionsupporting
confidence: 89%
“…However, contrary to conclusions from systematic reviews in MDD (Rock et al, 2014;Ahern and Semkovska, 2017), the present sample did not display objective attention deficits at baseline. Additionally, previous research has suggested distinct neurocognitive subgroups for MDD, with a majority showing near-normative performance on neuropsychological tests (Pu et al, 2018). Participants in the Return-to-Work program report less overall illness severity and are more likely to hold a job compared with other outpatients (Victor et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Major depressive disorder (MDD) is characterized by deficits in cognitive functions, including attention, memory, and executive functions (EF) (Snyder, 2012;Ahern and Semkovska, 2017). However, the heterogeneity of the cognitive profile in MDD appears to be large, with distinct neurocognitive subgroups (Pu et al, 2018). For those experiencing cognitive difficulties, deficits often persist into remission (Rock et al, 2014) and have a deleterious effect on everyday functioning (Baune et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…14 Data-driven studies in schizophrenia and more broadly defined psychotic disorders have typically separated patients into subgroups of global neurocognitive impairment, normal range ability and mixed or intermediate profiles. 1417 Recently, evidence of similar subgroups have been shown within samples of participants with depressive 18 and bipolar disorders, 19 and notably, across broader samples comprised of people with multiple major diagnostic groups. 2023 Taken together, these findings of homogeneous subgroups within diagnostic groups suggest that neurocognitive impairment may follow a continuum of severity distributed across mental disorders, with data-driven subgroups potentially representing a more useful level of analysis as regards neurocognition and associated factors.…”
Section: Data-driven Neurocognitive Subgroups In Mental Disordersmentioning
confidence: 97%